Accessing Battery Thermal Safety and Adoption of Socio-Technical Influence of Electric Vehicles in Nepal - Baral, Avishek; Kumar Jha, Ajay; Shrestha, Rahul (KEC Journal of Science and Engineering, 2026)
The adoption of electric vehicles (EVs) in Nepal faces critical challenges due to lithium-ion battery thermal instability, aggravated by steep terrain and high ambient temperatures. This study investigates a dual-enhancement passive Battery Thermal Management System (BTMS) using octadecane-based Phase Change Material (PCM) modified with graphite for thermal conductivity and polyurethane for flame retardancy. A 3D computational fluid dynamics (CFD) model of a 20-cell module was developed in ANSYS Workbench to evaluate discharge rates (1C–3C) under 25–40 ℃ ambient conditions. Results demonstrate that 10% graphite loading improved PCM conductivity by ~42%, achieving temperature uniformity within ±2 ℃, while a 5 mm polyurethane layer reduced simulated flame propagation by ~60%. Complementary stakeholder consultations revealed overheating and safety concerns as primary barriers to EV adoption, with a strong preference for passive, energy-efficient cooling solutions. By integrating technical optimization with socio-technical perspectives, this research provides a scalable framework for safer EV deployment in emerging economies. The findings highlight the potential of composite PCM-based BTMS to enhance user trust, support Nepal’s Net Zero 2045 target, and advance sustainable mobility, though experimental validation and long-term material stability remain essential future directions.